BIMBINGAN BAGI ANAK BERKELAINAN DI KELAS IV SEKOLAH DASAR NEGERI WELAI, KELURAHAN WELAI BARAT KECAMATAN TELUK MUTIARA - Tabita Asmiyanti Serangkai; Sintike Melani Mauyaru, Selfius Kolihar, Yessy Maata, Petrus Mau Tellu Dony, Halena Muna Bekata (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to discuss the guidance provided to children with disabilities in elementary schools, especially for Grade IV Students of Welai Public Elementary School, Alor Regency. The implementation of guidance for children with disabilities in elementary schools in general still faces several problems that hinder the achievement of learning objectives, such as the lack of a systematic program, the absence of special guidance and counseling teachers at the elementary school level who can specifically handle children with disabilities, and the low involvement of parents in Welai Public Elementary School. Guidance for children with disabilities in elementary schools (SD) is very important to help them achieve optimal development and independence.This guidance encompasses various aspects, including understanding individual needs, creating a supportive learning environment, and providing emotional support. This study employed qualitative methods, with descriptive qualitative data analysis. Data collection techniques included observation, interviews, and documentation to explore teachers' understanding of how they provide guidance to children with disabilities in the school environment.The results of the study indicate that the identification of children with disabilities is carried out through observation of children's daily behavior, interviews, and the use of simple instruments. Problems in the implementation of guidance for children with disabilities include the lack of counselor teachers to provide guidance for children with disabilities and schools do not have special programs for children with disabilities. The guidance program is more focused on an individual approach and collaboration with parents, even though the school does not yet have a special counselor teacher. The efforts of teachers and schools in overcoming problems by taking a structured and directed reinforcement approach, approaching children to understand their needs, and establishing communication with parents. This study recommends the need for government policies that support the existence of elementary school counselors and teacher training to handle children with disabilities.